Entrepreneurship Education: Economic Analys is of an Entrepreneurial Training Program based on Pupil Enterprises in Portugal - Susana Imaginário; Eurídice Cristo; Saul Neves de Jesus; Fátima Morais (Journal of Spatial and Organizational Dynamics, 2016)
Promoting creativity and entrepreneurship has been identified as being essential for the development of countries; therefore, it is crucial to implement entrepreneurship educational training projects. Based on this assumption, the Entrepreneurship in the School Program was design and implemented with 281 students and 7 teachers. The results of its development show that participation in this program successfully developed the participants’ creativity, so it was considered appropriate to examine the activity of each pupil enterprise more closely. Through this analysis we found that all the pupil enterprises achieved the project’s objectives and some progressed even further. In fact, due to their dynamism and proactivity, some pupil enterprises carried out strategies that allowed them to maximize their profit margin. The total profit obtained by the pupil enterprises was about €3,400, of which €739.90 were achieved by a single company. On the other hand, the pupil enterprises spent about €10,000 on products from their 39 local suppliers.